Altered Behavior Associated with Damage to the Ventromedial Hypothalamus: A Distinctive Syndrome - Frederick G. Flynn; Jeffrey L. Cummings; Uwamie Tomiyasu (Behavioural Neurology)
An adult manifested a tetrad of neurobehavioral findings consisting of episodic rage, emotional lability, hyperphagia with obesity, and memory impairment with intellectual decline following surgical removal of a craniopharyngioma. Post-mortem investigation of the topography of the lesion as well as review of previously reported cases suggest that this tetrad represents a specific neurobehavioral syndrome referable to damage to the ventromedial hypothalamus.